THE INTERTWINING OF ECO-SPIRITUALITY AND NON-HUMAN VOICES: A STUDY OF SELECTED POEMS FROM TED HUGHES’ CAVE BIRDS - Dhariwal, Jaibir (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ted Hughes’ Cave Birds emerges as a profound poetic exploration of the spiritual and environmental crises afflicting humanity in the 21st century. By intertwining eco-spirituality and non-human voices as material agency, Hughes crafts an alchemical drama that critiques anthropogenic cultural attitudes and highlights humanity’s estrangement from the natural world. Hughes’ spiritual belief in the sanctity and materiality of natural world has its own logic and validity. Tracing his deep awareness about ecological degradation, his poems treat the spiritual and environmental crisis as one. The poetry of Ted Hughes is fundamentally pitched against anthropocentrism, the root cause of environmental and spiritual crisis across the globe. Aligned with material ecocritical perspective, Hughes employs non-human voices to embody the agency of nature, challenging the anthropocentric perspective that places humanity at the centre of existence. Non-human entities in the poems serve not merely as metaphors but as active participants in a broader eco-spiritual dialogue, challenging the dominance of human-centric worldviews. This study explores how Hughes draws upon the ritualistic indigenous traditions to offer a critique of anthropocentric values and the mechanistic mindset of modernity while proposing an alternative vision of coexistence rooted in interconnectedness and harmony. Hughes envisions nature as both a victim and a healer, capable of offering relief to humanity’s spiritual and ecological disarray. Ultimately, Cave Birds serves as a poetic response to the ailing humanity of the 21st century, advocating for a reawakening of eco-spiritual consciousness as a path to both ecological and spiritual restoration.